Biallelic variants in COX4I1 associated with a novel phenotype resembling Leigh syndrome with developmental regression, intellectual disability, and seizures. Issue 10 (10th July 2019) - Pillai, Nishitha R.; AlDhaheri, Noura S.; Ghosh, Rajarshi; Lim, Jaehyung; Streff, Haley; Nayak, Anuranjita; Graham, Brett H.; Hanchard, Neil A.; Elsea, Sarah H.; Scaglia, Fernando
Abstract: Autosomal recessive COX4I1 deficiency has been previously reported in a single individual with a homozygous pathogenic variant in COX4I1, who presented with short stature, poor weight gain, dysmorphic features, and features of Fanconi anemia. COX4I1 encodes subunit 4, isoform 1 of cytochrome c oxidase. Cytochrome c oxidase is a respiratory chain enzyme that plays an important role in mitochondrial electron transport and reduces molecular oxygen to water leading to the formation of ATP. Defective production of cytochrome c oxidase leads to a variable phenotypic spectrum ranging from isolated myopathy to Leigh syndrome. Here, we describe two siblings, born to consanguineous parents, who presented with encephalopathy, developmental regression, hypotonia, pathognomonic brain imaging findings resembling Leigh‐syndrome, and a novel homozygous variant on COX4I1, expanding the known clinical phenotype associated with pathogenic variants in COX4I1 .